STOCHASTIC CALCULATION OF A QUASI-HOMOGENEOUS BOLTED JOINTS OF THE BODY SHEETS OF THE STEEL SILOS (Academic journal Industrial Machine Building Civil Engineering, 2019)
This paper deals with the study of reliability of quasi-homogeneous bolted joints of the body of thin-walled constructions ofthe steel silos. Heterogeneity of this unit can be caused by number of reasons, in particular by presence of bolts of differentstrength in joint. In such case the reliability of the system is determined trough the probability of trouble-free work of the coefficient of the critical factor. The general conception of stochastic calculation consists in using the Monte-Karlo simulationprocedure for the samples of random values of the large volume. It was formed the system of conditions, under which the reliability of joints is provided and analytical expressions for the value of coefficient of the critical factor is got, and also madepractical calculation example with the following graphic presentation on a special coordinate plane – a critical stochasticscale. It was illustrated that random presence of bolts of less strength in field joint rapidly increases the risk of refusal.
Keywords: cylindrical silos; reliability; stochastic calculation; probability of the trouble-free work; quasi-homogeneous; bolted joint; coefficient of the critical factor